SULTAN MUHAMMAD BAHAUDIN : KONTRIBUSINYA TERHADAP KESULTANAN PALEMBANG DARUSSALAM - Fitriani (Program Studi Sejarah Peradaban Islamm UIN Raden Fatah Palembang, 2023)
This article discusses the Struggle of Sultan Muhammad Bahauddin and His Contribution to the Sultanate of Palembang Darussalam (1188-1218H/1774-1803 AD). The main problem raised in this research is how the struggle and contribution of Sultan Muhammad Bahauddin to the Sultanate of Palembang Darussalam. The type of research used is qualitative research, namely the type of research that explains the facts between the phenomena under study and to understand the phenomenon of what the research subject experienced by describing and collecting data through primary sources in the form of HIKAYAT PALEMBANG and secondary sources in the form of articles, books and documentation in the form of pictures. Sultan Muhammad Bahaudin's contribution to the Palembang Darussalam Sultanate had a major influence on the Sultanate. From the results of this study, it can be concluded that Sultan Muhammad Bahauddin had a sizeable contribution in fighting for the Palembang Darussalam Sultanate. One of the things we can feel is the development he carried out in the form of Fort Kuto Besak (BKB) to an increasingly advanced economy like Tin and Pepper which was successfully monopolized by Sultan Muhammad besides that the political elite could also be controlled and respected by other nobles, Palembang was also the center for broadcasting Islam in the archipelago thanks to him, besides that Sultan Muhammad Bahauddin also made medical texts about concoctions for knee pain, bone pain or gout is a medical text made by Sultan Muhammad Bahauddin to Sheikh Muhammad Akib.